2005
DOI: 10.1079/phn2004695
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between household budget survey and 24-hour recall data in a nationally representative sample of Polish households

Abstract: Objective: Household budget survey (HBS) data are used regularly for nutritional epidemiological purposes. The validity of HBS data, however, is not well established. The aim of this project was to compare HBS and individual nutrition survey (INS) data in a nationally representative sample of Polish households. Design: Estimates of food consumption and nutrient intake were compared between household food acquisition data collected over 1 month and a single 24-hour recall collected from every household member i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 2 publications
2
36
0
Order By: Relevance
“…Higher values for fats and oils in HBS data were also reported in Sweden (Becker 2001), Poland (Sekula et al 2005) and Spain (Serra-Majem et al 2003). In comparison with HBS, an underreporting of sodium intake was also found in the Polish individual dietary data (Sekula et al 2005).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Higher values for fats and oils in HBS data were also reported in Sweden (Becker 2001), Poland (Sekula et al 2005) and Spain (Serra-Majem et al 2003). In comparison with HBS, an underreporting of sodium intake was also found in the Polish individual dietary data (Sekula et al 2005).…”
Section: Discussionmentioning
confidence: 67%
“…In fact, even when comparing data from a different assessment level taken from the same sample, as in the case of individualbased further evaluation of HBS subsamples (Sekula et al 2005;Becker 2001;Nelson 1986), or at the same assessment level but from different sources (Paterakis and Nelson 2003;Sekula et al 1991), agreement is never absolute and no obvious explanations for this can always be found.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The comparison between national household budget and individual nutrition surveys in four European countries showed good correlations between data sources for almost all food groups (NASKA et al, 2001). A study from Poland, on the other hand, found different results, showing discrepancies between data sources for many food groups (SEKULA et al, 2005).…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…In addition, food acquisition surveys do not account for waste from cooking, spoilage, or leftover, and meals not eaten at home. Analyses of a limited 143 number of countries and food groups suggested that household budget surveys estimates can significantly differ from individual dietary consumption (BECKER, 2001;CLARO et al, 2010;NASKA et al, 2001;SEKULA et al, 2005).…”
Section: Monitoring Population Dietary Patterns: the Importance Of Thmentioning
confidence: 99%